Additional knowledge on the Egyptian mongoose Herpestes ichneumon (Linnaeus, 1758) from the Jordan River, Jordan - Eid, Ehab; Alayyan, Mohammad Farid; Damhoureyeh, Said A. (Nepalese Journal of Zoology, 2024)
The Egyptian mongoose (Herpestes ichneumon) is globally assessed as Least Concern, yet within Jordan, it has been classified as Endangered due to its limited extent of occurrence and rapid habitat degradation. Using camera traps, this study was conducted from 01 June 2020 to 28 February 2022 on a private farm in the Sheikh Hussein area along the lower Jordan River. Despite challenges such as dense reed growth, farm activities, and the presence of workers and roaming dogs, we successfully captured photographic evidence of the Egyptian mongoose displaying various social behaviors, including group and solitary sightings. The species exhibited a diurnal activity pattern and coexisted with other carnivores, such as the golden jackal (Canis aureus), jungle cat (Felis chaus), and red fox (Vulpes vulpes). Our data suggest a small local population, potentially comprising the four individuals observed, vulnerable to localized threats like incidental poisoning and habitat changes due to farming. To mitigate these risks, we recommend implementing Other Effective Area-based Conservation Measures (OECMs) as a tool beyond Jordan's national protected area network to achieve effective and sustained long-term in situ biodiversity conservation outcomes in partnership with the military.